Rethinking the euro as a common currency for Europe: Keynes’s Plan revisited - Rossi, Sergio (Revista de Economía Crítica, 2024)
This paper sets off from the monetary–structural origins of the euro-area crisis, which is not a sovereign debt crisis, but a crisis due to a lack of payment finality at international level. The first section explains that international payments across the euro area are not, to date, final for the countries concerned, as the European Central Bank does not operate as settlement institution for the national central banks involved thereby. The exploding TARGET2 imbalances observed in the aftermath of the euro-area crisis are an empirical evidence of this monetary–structural flaw. The second section suggests therefore that at the euro-area level there should be an international monetary institution issuing the euro as a common (instead of a single) currency for the euro-area member countries. Thereby those countries that are currently much in trouble within the euro area may reintroduce a national currency that allows them to recover monetary-policy sovereignty as a tool that can be used, together with fiscal policy, to steer the domestic economy in the country’s own interest. The third section concludes with some policy-oriented remarks, putting to the fore the major merits of transforming the euro from a single into a common currency in order to contribute to European (monetary) integration for the common good.